Circulating plasma exosomal long non-coding RNAs LINC00265, LINC00467, UCA1, and SNHG1 as biomarkers for diagnosis and treatment monitoring of acute myeloid leukemia - Xiao, Qiaoling; Lin, Can; Peng, Meixi; Ren, Jun; Jing, Yipei; Lei, Li; Tao, Yonghong; Huang, Junpeng; Yang, Jing; Sun, Minghui; Wu, Jing; Yang, Zailin; et al. (Frontiers in Oncology, 2022)
Exosomal long non-coding RNAs (lncRNAs) have emerged as a cell-free biomarker for clinical evaluation of cancers. However, the potential clinical applications of exosomal lncRNAs in acute myeloid leukemia (AML) remain unclear. Herein, we attempted to identify plasma exosomal lncRNAs as prospective biomarkers for AML. In this study, plasma exosomes were first successfully extracted from AML patients and healthy donors (HD). Subsequently, the downregulated plasma exosomal lncRNAs (LINC00265, LINC00467, and UCA1) and the upregulated plasma exosomal lncRNA (SNHG1) were identified in AML patients (n=65) compared to HD (n=20). Notably, individual exosomal LINC00265, LINC00467, UCA1, or SNHG1 had a capability for discriminating AML patients from HD, and their combination displayed better efficiency. Furthermore, exosomal LINC00265 and LINC00467 were increased expressed in patients achieving complete remission after chemotherapy. Importantly, there was upregulation of exosomal LINC00265 and downregulation of exosomal SNHG1 upon allogeneic hematopoietic stem cell transplantation. Additionally, these lncRNAs were high stability in plasma exosomes. Exosomal LINC00265, LINC00467, UCA1, and SNHG1 may act as promising cell-free biomarkers for AML diagnosis and treatment monitoring and provide a new frontier of liquid biopsy for this type of cancer.